Chaos Theory in Engineering Project Management: A Review of Nonlinear Dynamics and Predictability - Hosseini, Mostafa; Memarnejad, Mostafa (Management Strategies and Engineering Sciences, 2023)
Chaos theory, which examines the behavior of dynamical systems that are highly sensitive to initial conditions, provides a powerful framework for understanding the complexities and unpredictability inherent in engineering project management. This narrative review explores the application of chaos theory to engineering projects, focusing on nonlinear dynamics, predictability, and uncertainty management. By synthesizing the literature, the review highlights the limitations of traditional linear approaches in predicting project outcomes and underscores the importance of adaptive and flexible management strategies to cope with chaos-induced uncertainties. The review also discusses tools such as scenario planning, risk management frameworks, and robust design techniques, which enhance project resilience in the face of chaos.